KUALITAS TIDUR ORANG DEWASA DENGAN HIPERTENSI - Septiastuti, Dinda Miranda; Neri, Ervina Lili; Fauzan, Suhaimi (Sekolah Tinggi Ilmu Keperawatan Muhammadiyah Pontianak, 2025)
Background : Poor sleep quality can be related to health conditions such as hypertension. Objective : To determine the relationship between sleep quality and the incidence of hypertension in adults at the Tanjung Hulu Community Health Center, East Pontianak. Method : This research uses an analytical observational research design with a cross-sectional study approach, namely the independent variable as risk and the dependent variable as effect. A total of 96 adult respondents were research subjects using a sleep quality questionnaire (PSQI) and blood pressure results in medical records. The data analysis technique used is univariate analysis and bivariate analysis using the Kendall's Tau-B test. Results : Based on the results of the analysis using the Kendall's Tau-B statistical test, the P value = 0.387 and the r value = - 0.089. Respondent characteristics including age were mostly 51.0% aged 36-45 years. Most of them are female, 71.9%. Most have jobs as much as 62.5%. Conclusion : There is no relationship between sleep quality and the incidence of hypertension in adults at the Tanjung Hulu Community Health Center, East Pontianak. Keywords : Sleep Quality, Incidence of Hypertension, Adults